(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The paper examines the foundations and limits of the right to donate excised body parts and products for biomedical purposes, exploring, under a comparative law perspective, the donators’ right to control their human biological materials. The essay takes a unique approach by investigating the unregulated hypothesis of donation to the science of amputated limbs to assess whether allocating such anatomical body parts to biomedical study and research activities falls within the individual’s self-determination or the discretion of medical professionals.